Phytochemicals, antioxidant capacity and cytoprotective effects of jackfruit (Artocarpus heterophyllus Lam.) axis extracts on HepG2 cells. (June 2021) - Li, Ziwei; Lan, Yaqi; Miao, Jianyin; Chen, Xiaoman; Chen, Bingbing; Liu, Guo; Wu, Xian; Zhu, Xiaoai; Cao, Yong
Abstract: Jackfruit ( Artocarpus heterophyllus Lam .) is an underutilized edible fruit in the tropics and subtropics. The aim of this study was to explore the chemical composition, antioxidant capacity and cytoprotective effects of jackfruit extracts. Based on DPPH assay, it was found that jackfruit axis extract showed the strongest antioxidant activity, and 53 main compounds were identified by the HPLC-MS/MS. The extract showed excellent antioxidant activities in DPPH (IC50  = 2.871 mg/mL), ABTS (IC50  = 0.259 mg/mL), ferrous ion chelation (IC50  = 2.164 mg/mL) and ORAC (48.19 μmol of TE) assays. The CAA assay showed that the extract possesses a potent antioxidant activity (EC50  = 2.074 μg/mL) in HepG2 cells. Additionally, 70 μg/mL jackfruit axis extract protected cells against alcohol-induced cytotoxicity and its protection was even more efficacious than that of vitamin C. Overall, these results indicated that the jackfruit axis extract has great potential for use as functional foods. Highlights: The antioxidant activity of different parts in jackfruit was firstly studied. 53 bioactive compounds were determined in jackfruit axis extract. The antioxidant activity was evaluated by chemical analysis and cell experiments. The jackfruit axis extract showed potential for use as a natural antioxidant agent.